Pariwisata dan Ketahanan Pangan: Potensi Wisata Berbasis Ekonomi Sirkular dan Kesehatan Di Desa Wukirsari, Kapanewon Cangkringan, Kabupaten Sleman - Pitaya; Cipta Pramana (STIE Pariwisata API Yogyakarta, 2025)
Wukirsari Village, Cangkringan Subdistrict, Sleman Regency, is a rural area on the southern slopes of Mount Merapi. This village has long been known as a buffer zone for various agricultural products, especially rice. Its direct border with Umbulharjo Village, where the Pentingsari Tourism Village is located, makes Wukirsari a strategically located village. Road access, community-operated accommodations, restaurants, and other essential elements of a tourist attraction are all within relatively close proximity. Nearly every corner of Wukirsari Village offers a variety of unique tourism potential. In addition to the expanse of local rice fields thriving with a variety of crops, this area also offers other potential not found in other villages on the southern slopes of Mount Merapi. These potentials are environmental conservation and educational tourism attractions, namely the Javan Barn Owl (Tyto alba) monitoring center, a bamboo grove cultivation site, and the Mazaarat Artisan Cheese factory, which are closely related to food security issues. However, ironically, until now these potentials have not been optimally developed. Even in Wukirsari, there is not a single tourist village managed by the community as a local tourism movement entity. Therefore, this study seeks to achieve the following objectives: 1) Conducting an inventory and identification of tourism potential, 2) Developing existing tourism potential on a commercial scale by involving the local community, and 3) Incorporating circular economy principles in every development undertaken. The methods used included direct field observation, in-depth interviews with tourism stakeholders, documentation, and pilot testing. This research is expected to lead to the development of community-based tourism based on circular economy principles, providing new experiences for both tourists and local communities, the primary operators. This will enable the continued growth of environmentally friendly tourism alongside food security.